2017
DOI: 10.1126/science.aaf6407
|View full text |Cite
|
Sign up to set email alerts
|

A SUMO-ubiquitin relay recruits proteasomes to chromosome axes to regulate meiotic recombination

Abstract: Meiosis produces haploid gametes through a succession of chromosomal events, including pairing, synapsis, and recombination. Mechanisms that orchestrate these events remain poorly understood. We found that the SUMO (small ubiquitin-like modifier)–modification and ubiquitin-proteasome systems regulate the major events of meiotic prophase in mouse. Interdependent localization of SUMO, ubiquitin, and proteasomes along chromosome axes was mediated largely by RNF212 and HEI10, two E3 ligases that are also essential… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
205
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(228 citation statements)
references
References 42 publications
17
205
0
6
Order By: Relevance
“…Therefore, it is clear that MOF and ZYGO1 play distinct roles during meiosis in rice. Interestingly, recent studies reported that chromosomally tethered proteasomes promote pairing and recombination in mouse, budding yeast, and C. elegans, suggesting that the meiotic programmed degradation event is highly conserved among species (Ahuja et al, 2017;Rao et al, 2017). We also found that ZYGO1 shows limited sequence similarity to FBL12 in mouse.…”
Section: Zygo1 Promotes Bouquet Formation Within An Scf Complexmentioning
confidence: 48%
“…Therefore, it is clear that MOF and ZYGO1 play distinct roles during meiosis in rice. Interestingly, recent studies reported that chromosomally tethered proteasomes promote pairing and recombination in mouse, budding yeast, and C. elegans, suggesting that the meiotic programmed degradation event is highly conserved among species (Ahuja et al, 2017;Rao et al, 2017). We also found that ZYGO1 shows limited sequence similarity to FBL12 in mouse.…”
Section: Zygo1 Promotes Bouquet Formation Within An Scf Complexmentioning
confidence: 48%
“…Plants, fungi, and invertebrates possess a single HEI10/ RNF212 ortholog (Bhalla et al 2008;Chelysheva et al 2012;Wang et al 2012;Serrentino et al 2013;De Muyt et al 2014;Lake et al 2015), whereas vertebrates encode separate RNF212 and HEI10 proteins that function as antagonistic SUMO and ubiquitin E3 ligases (Ward et al 2007;Reynolds et al 2013;Qiao et al 2014;Gray and Cohen 2016;Rao et al 2017). In mice, HEI10 and RNF212 promote stable accumulation of MSH4/MSH5 (MutSγ) heterodimers on recombining meiotic chromosomes via a SUMO-ubiquitin relay, which promotes recruitment of MLH1/MLH3 (MutLγ) and crossover formation (Ward et al 2007;Reynolds et al 2013;Qiao et al 2014;Gray and Cohen 2016;Rao et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As HEI10 belongs to a conserved gene family, which encodes RING domain SUMO/ubiquitin E3 ligases that promote crossovers in diverse eukaryotes, this was the strongest candidate gene for rQTL1 (Supplemental Figs. S2, S3;Bhalla et al 2008;Kong et al 2008;FledelAlon et al 2011;Chelysheva et al 2012;Sandor et al 2012;Serrentino et al 2013;De Muyt et al 2014;Qiao et al 2014;Johnston et al 2016;Rao et al 2017). HEI10 family proteins possess N-terminal RING domains, central coiled-coil domains, and C-terminal regions of unknown function (Supplemental Figs.…”
Section: Genetic Mapping Of Arabidopsis Recombination Quantitative Trmentioning
confidence: 99%
“…In mammals, every chromosome pair obtains many recombination sites but generally yields only one to two crossover sites (Kauppi et al, 2004). Designations of which recombination sites become crossovers involve antagonistic roles between ubiquitin E3 ligase HEI10 and SUMO E3 ligase RNF212 (Reynolds et al, 2013;Qiao et al, 2014;Rao et al, 2017;Ahuja et al, 2017). It is possible that the SMC5/6 complex is a substrate of HEI10 and RNF212.…”
Section: Smc5/6 Localization Pattern Implicates Multiple Functions Dumentioning
confidence: 99%